2019
DOI: 10.1111/exd.13819
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide for photoprotection and skin cancer chemoprevention: A review of efficacy and safety

Abstract: Nicotinamide is a water‐soluble vitamin B3 derivative that has many roles in medicine. This review examines the role of nicotinamide in dermatology and its actions in preventing photoageing and skin cancers in humans. Nicotinamide prevents ultraviolet radiation (UV) from reducing ATP levels and inhibiting glycolysis, thus preventing the UV radiation‐induced energy crisis. This enhances DNA repair and reduces UV‐induced suppression of immunity. Randomised controlled clinical trials have also shown that nicotina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 58 publications
1
48
0
1
Order By: Relevance
“…NAM is a water-soluble form of Vitamin B3 (niacin) that can be found in animal and plant food, also as a cost-effective vitamin supplement [37][38][39]. It is absorbed in the stomach or intestine, metabolized in the liver, and excreted through the kidneys [40,41]. While its presence is vital for cellular energy metabolism, lack of NAM is associated with fatigue and anorexia.…”
Section: Nam Basic Principles and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…NAM is a water-soluble form of Vitamin B3 (niacin) that can be found in animal and plant food, also as a cost-effective vitamin supplement [37][38][39]. It is absorbed in the stomach or intestine, metabolized in the liver, and excreted through the kidneys [40,41]. While its presence is vital for cellular energy metabolism, lack of NAM is associated with fatigue and anorexia.…”
Section: Nam Basic Principles and Metabolismmentioning
confidence: 99%
“…In contrast, high oral doses of NAM, especially above 6 g/day, have been associated with gastrointestinal toxicity [40]. Adverse effects such as flushing, hypotension or headache due to vasodilation are believed to be caused by nicotinic acid (another form of vitamin B3, also a NAD + precursor) rather than the NAM itself [39,41,47].…”
Section: Nam Basic Principles and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The NIA treatment decreased TEWL values, increased the thickness of the SC, and larger and more mature corneocytes were found in the treated versus control sites. More recently, evidence from a phase 3 randomized clinical trial points to NIA having a role in the prevention of non-melanoma skin cancer [6,7]. The discovery and development of robust and accessible human skin surrogates continues to be an area of considerable interest to industry and regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Nicotinamide (Nam; aka niacinamide, vitamin B3) has been used for decades in cosmetic and pharmaceutical products for the treatment of acne, skin photoaging attributes, and barrier integrity improvement [12][13][14]. It has been reported that Nam can protect cells from oxidative stress, UVinduced immunosuppression, and metabolic disruption [15][16][17]. Additionally, Nam has been shown to inhibit inflammatory cytokine induction by endotoxin in red blood cells [18].…”
mentioning
confidence: 99%